Participation in Environmental Organizations: An Empirical Analysis - Benno Torgler; María A. García-Vali\~nas (Center for Research in Economics, Management and the Arts (CREMA), 2006)
The literature on volunteering has strongly increased in the last few years. However, there is still a lack of substantial empirical evidence about the determinants of environmental participation. This empirical study analyses a cross-section of individuals using micro-data of the World Values Survey wave III (1995-1997), covering 38 countries, to investigate this question. The results suggest that not only socio-demographic and socio-economic factors have an impact on individuals' active participation in environmental organizations, but also political attitudes. Furthermore, regional differences are observed.
Keywords: Q26; R22; Z13; I21; 330; Environment; Environmental Participation; International Perspective; Political Interest; Social Capital